A randomised phase IIb study of mavrilimumab, a novel GM–CSF receptor alpha monoclonal antibody, in the treatment of rheumatoid arthritis. Issue 6 (17th February 2017) - Burmester, Gerd R; McInnes, Iain B; Kremer, Joel; Miranda, Pedro; Korkosz, Mariusz; Vencovsky, Jiri; Rubbert-Roth, Andrea; Mysler, Eduardo; Sleeman, Matthew A; Godwood, Alex; Sinibaldi, Dominic; Guo, Xiang; et al.
Abstract : Objectives: Despite the therapeutic value of current rheumatoid arthritis (RA) treatments, agents with alternative modes of action are required. Mavrilimumab, a fully human monoclonal antibody targeting the granulocyte–macrophage colony-stimulating factor receptor-α, was evaluated in patients with moderate-to-severe RA. Methods: In a phase IIb study (NCT01706926 ), patients with inadequate response to ≥1 synthetic disease-modifying antirheumatic drug(s), Disease Activity Score 28 (DAS28)−C reactive protein (CRP)/erythrocyte sedimentation rate ≥3.2, ≥4 swollen joints despite methotrexate (MTX) were randomised 1:1:1:1 to subcutaneous mavrilimumab (150, 100, 30 mg), or placebo every other week (eow), plus MTX for 24 weeks. Coprimary outcomes were DAS28−CRP change from baseline to week 12 and American College of Rheumatology (ACR) 20 response rate (week 24). Results: 326 patients were randomised (150 mg, n=79; 100 mg, n=85; 30 mg, n=81; placebo, n=81); 305 completed the study (September 2012–June 2013). Mavrilimumab treatment significantly reduced DAS28−CRP scores from baseline compared with placebo (change from baseline (SE); 150 mg: −1.90 (0.14), 100 mg: −1.64 (0.13), 30 mg: −1.37 (0.14), placebo: −0.68 (0.14); p<0.001; all dosages compared with placebo). Significantly more mavrilimumab-treated patients achieved ACR20 compared with placebo (week 24: 73.4%, 61.2%, 50.6% vs 24.7%, respectively (p<0.001)). Adverse events were reported in 43 (54.4%), 36 (42.4%), 41 (50.6%) and 38 (46.9%) patients in the mavrilimumab 150, 100, 30 mg eow and placebo groups, respectively. No treatment-related safety signals were identified. Conclusions: Mavrilimumab significantly decreased RA disease activity, with clinically meaningful responses observed 1 week after treatment initiation, representing a novel mechanism of action with persuasive therapeutic potential. Trial registration number: NCT01706926 ; results.